ISLAMIC ARCHITECTURE: SHAPING CULTURAL IDENTITY, FOSTERING COMMUNITY COHESION, AND PROMOTING INCLUSIVITY - Awaliyah, Dian Nafiatul (JIAA: Journal of Islamic Art and Architecture, 2023)
This paper explores the multifaceted role of Islamic architecture as a symbol of cultural and religious identity, emphasizing its significance in fostering community cohesion and inclusivity. How does Islamic architecture reflect cultural and religious identity and contribute to community cohesion and inclusivity? The objective is to analyze the principles, values, and adaptability of Islamic architecture within the context of cultural diversity and modernity, emphasizing its role in preserving identity and promoting unity. A qualitative research approach was employed, involving a comprehensive review of literature and analysis of historical and contemporary examples of Islamic architecture worldwide. The study incorporated architectural design principles, cultural influences, and societal impacts as key analytical lenses. Islamic architecture transcends mere physical structures; it embodies core values such as privacy, neighborhood rights, social solidarity, moderation, equity, sincerity, and aesthetic values. Mosques, in particular, symbolize faith and serve as spaces for communal worship and engagement. This architectural heritage demonstrates the adaptability of Islamic architecture to diverse cultural influences while retaining its distinctive identity. Moreover, it continues to evolve, expressing local Islamic identities and meeting the needs of modern society. Islamic architecture plays a pivotal role in fulfilling the determinations of the Holy Scriptures and forging sacred connections with individuals. It fosters a profound sense of belonging, spirituality, and inclusivity within the Muslim community, contributing to cultural heritage and unity that transcends borders and time.